Life table of podfly (Melanagromyza obtusa) infesting pigeonpea (Cajanus cajan) - KUMAR, AKHILESH; NATH, PARAS (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1994-95 and 1995-96 to study life tables of padfly (Melanagramyza obtusa Malloch) infesting pigeonpea [Cajanus cajan (L.) Millsp.] fields. The action of mortality factors operating in each of the 2 generation was found different. During the first and the second generations the key mortality factors were the hatching fallure of the eggs because of sterillity of sterilly, desication and death and parasitization of hte newly hatched youngerm larvae and the older larvae nu Euderus lividus (Ashm.) (Eulophidae: Hymenoptera). The pupal mortaity was due to the parasitization by E. lividus and the unknown causes. The mortality was more (8.80% and 6.38% in hte first generation and 8.09 and 7.47A% in the second generation due to E. lividus and 38.00% and 34.04% in the first generation and 34.10 and 32.03% the second generationdue to unknown causes during 1994-95 and 1995-96 respectively) in the younger larvae. followed by the older larvae (6.67% and 4.47% due to E. lividus and 17.67% and 19.05% due to unknown causes in the first generation and 7.00% and 6.47% due to E. lividus and 13.00% and 10.05% due to unknown couses in the second generation during 1994-95 and 1995-96 respectively). The pupal mortality was 4.35% and 4.68% due to E. lividus and 23.91% and 19.75% due to unknown causes in the first generation and 5.00% and 5.67% due to E. lividus and 20.00% and 17.02% due to known causes during 1994-95 and 1995-96 respectively. The trend index was positive in both the generations and it was higher in the generation than the second generation.